Long Non-coding RNAs: At the Heart of Cardiac Dysfunction? - Hobuß, Lisa; Bär, Christian; Thum, Thomas (Frontiers in Physiology, 2019)
During the past decade numerous studies highlighted the importance of long noncoding RNAs (lncRNAs) in orchestrating cardiovascular cell signaling. Classified only by a transcript size of more than 200 nucleotides and their inability to code for proteins, lncRNAs constitute a heterogeneous group of RNA molecules with versatile functions and interaction partners, thus interfering with numerous endogenous signaling pathways. Intrinsic transcriptional regulation of lncRNAs is not only specific for different cell types or developmental stages, but may also change in response to stress factors or under pathological conditions. Regarding the heart, an increasing number of studies described the critical regulation of lncRNAs in multiple cardiac disorders, underlining their key role in the development and progression of cardiac diseases. In this review article, we will summarize functional cardiac lncRNAs with a detailed view on their molecular mode of action in pathological cardiac remodeling and myocardial infarction. In addition, we will discuss the use of circulating lncRNAs as biomarkers for prognostic and diagnostic purposes and highlight the potential of lncRNAs as a novel class of therapeutic targets for therapeutic purpose in heart diseases.